Assessment of methods to measure adherence of antidepressants: a systematic review - Abdul Ghafur, Nur Aina; Zaini, Syahrir; Ahmad Mizher, Hussam Abdeljabar (Kulliyyah of Pharmacy, IIUM, 2024)
Introduction: Adherence towards antidepressant agents is a vital element in effectively managing depression. Non-adherence of antidepressants can lead to a recurrence of depressive symptoms and decreased treatment effectiveness. Adherence is assessed using various types of measures. This study aims to evaluate the different methods used to assess the adherence towards antidepressants on adults with depression. Method: “This systematic review adhered to the guidelines outlined in the PRISMA statement. “PubMed, Cochrane Library, and Scopus are searching from 2013 to 2023 for articles that studied or reported on antidepressant adherence measures in adults with depression. Two authors conducted independent screenings of the articles against the eligibility criteria, examining titles, abstracts, and full texts. “The risk of bias for all included studies were assessed using the Joanna Briggs Institute (JBI) critical appraisal checklists. “Information from all the selected articles was extracted using a predefined table. Results: 15 studies met the eligibility criteria. When measuring adherence towards antidepressant at initiation and/or implementation phase, “self-report methods such as Medication Adherence Rating Scale (MARS) demonstrated acceptable reliability and validity, while Brief Medication Questionnaire (BMQ by Svarstad et al.), Morisky Medication Adherence Questionnaire (MAQ), and Brief Adherence Rating Scale (BARS) showed good validity, and Morisky Medication Adherence Scale (MMAS), Morisky Green Levine Adherence (MGLA), Beliefs about Medicine Questionnaire (BMQ by Horne et al.) and Drug Attitude Inventory (DAI-10) showed good reliability.” Conclusion: This study found a diverse range of methods to measure adherence towards antidepressant in adults. Self-report assessments, particularly in primary care and psychiatric settings, emerged as the most practical tools followed by clinician-rating scale, pharmacy refill data, adherence scale, pill count, and average serum level. No single measure with consistently shown strong reliability and validity across different adherence stages, highlighting the need for a combined approach.